Bestiarium Zofii Nałkowskiej - Janowska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2005)
The thesis deals with motives of animals in Zofia Nałkowska’ s works. The motives which constitute a part of strategy used for the presentation that depicts one of the most ambiguous categories in the 20th century literary analysis. The main animal motives found in Nalkowska’s writings include pictures of fish, horses, butterflies, insects ans Swiss birds called „choucas”. All whose symbols have been discussed in this thesis from the feminist, or generally concerning women perspective, as well as the symbols related to war and wide category of empathy. The association of animal motives with the characteristic features of Nałkowska’s poetry and as well as her imagination contributed to the formation of a statement that there exist positive aspects of animal motives. The above mentioned motives, which are commonly based on customs, traditions, language variations, ancient tales, biblica pictures and bestiaries, together with the comments of the writers of “Młoda Polska” remain a vivid element of still ongoing discussion pertaining to the power of calamities, on one hand, and the psychological as well as phisical condition of a man. Nałkowska contributes to all the above mentioned traditions taking advantage of her own experience and consistently creating her own philosophy of a human being.